Brønsted Acid‐Catalyzed Direct C(sp2)−H Heteroarylation Enabling the Synthesis of Structurally Diverse Biaryl Derivatives. Issue 1 (20th November 2018) - Yuan, Shuo; Yu, Bin; Liu, Hong‐Min
Abstract: Biaryl scaffold is an important class of structural frameworks that exists in many natural products and drug molecules. The development of transition metal‐catalyzed approaches for the efficient construction of biaryl scaffolds has long been pursued because of the interesting structural features and broad biological profiles of biaryl scaffolds. Herein, we describe the Brønsted acid‐catalyzed direct C( sp 2 )−H heteroarylation that enables the synthesis of biaryl fragments (70 examples) in moderate to excellent yields (up to 99% yield), which was also performed at a gram scale and successfully applied to the privileged quinazoline scaffolds of the first‐generation epidermal growth factor receptor (EGFR) inhibitors Gefitinib and Erlotinib, offering rapid access to a series of quinazoline‐based biaryl compounds. Additionally, the late‐stage diversifications were performed based on the compound 3 b, generating a library of structurally diverse and complex biaryl compounds. Abstract :